Socially Responsible Investing - Passing Vogue or Long-term Trend? - Duliniec, Aleksandra (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The dynamic growth of socially responsible investing has been observed globally in the last decade. The determinants of such investment decisions are described in the paper. A variety of criteria - both negative and positive - can be used in putting together a portfolio. The positive screening of companies to be included in a socially responsible portfolio is based mainly on environmental, social and governance (ESG) issues. However, because there is no explicit evidence that ethical (responsible) funds generate higher returns than conventional funds, it is worth considering the future of socially responsible investments. Will they continue to grow or, after a period of increased interest in social and ethical factors (undoubtedly as the result of the global financial crisis), will they lose their appeal? The paper discusses that issue.